2010
DOI: 10.1111/j.1468-0394.2009.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Open architecture computer‐aided diagnosis system

Abstract: In this study an approach to open architecture computer-aided diagnosis (CAD) is presented. The traditional goal of a CAD system, to assist the physicians in performing the diagnosis and treatment, has been extended. The platform also supports the system designer in developing a new CAD workflow by implementing general-purpose modules as well as problem-dependent procedures. A new CAD may require new procedures to be added, yet some of the already implemented functions can be employed. The CAD environment is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Pietka et al (2010), in their paper ‘Open architecture computer‐aided diagnosis system’, extend the traditional goal of a computer‐aided diagnosis (CAD) system to assist physicians in performing diagnosis and treatment. The presented platform helps the system designer in developing a new CAD workflow by implementing general‐purpose modules as well as problem‐dependent procedures.…”
Section: The Papersmentioning
confidence: 99%
“…Pietka et al (2010), in their paper ‘Open architecture computer‐aided diagnosis system’, extend the traditional goal of a computer‐aided diagnosis (CAD) system to assist physicians in performing diagnosis and treatment. The presented platform helps the system designer in developing a new CAD workflow by implementing general‐purpose modules as well as problem‐dependent procedures.…”
Section: The Papersmentioning
confidence: 99%
“…overall and detailed motion characteristics, activity time distribution, etc. To do so, a remotely accessible computer-aided diagnosis (CAD) [25] AAL system has been proposed [24], employing mobile data acquisition devices with inertial sensors at the lowest level of the architecture. Preliminary study on signal personalization in feature domain has been reported in [26].…”
Section: Introductionmentioning
confidence: 99%
“…While these are highly accurate and fast, they still require experienced and competent medical practitioners for the proper interpretation [4]. Thus, computer aided diagnosis is significantly useful due to the fact that it could enhance the results of humans in such domain [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The involvements of information technology in the development of various applications have completely changed the world. The noticeable reasons for the introduction of computer systems are reliability, accuracy, simplicity and ease of use [5][6][7]. Moreover, it has become almost compulsory to use computers to assist radiological experts in clinical diagnosis and treatment planning due to the increasing use of imaging for diagnosis, treatment planning and clinical studies [8,9].…”
Section: Introductionmentioning
confidence: 99%